Prospectus 2009/2010 : Distance Education Centre : Gateway to Opportunity / Institute of Education Development, UiTM - Institute of Education Development, UiTM (Institute of Education Development (InED), UiTM, 2009)
This illustrative and comprehensive prospectus is our way of assisting prospective students to have a better understanding on the courses and programmes offered in MARA University of Technology via distance learning. It is hoped that this prospectus will be handy in answering all your initial questions about InED, and about the programmes you are about to follow. InED, UiTM, will continue to ensure that there are opportunities for bumiputras to acquire new knowledge. Improve their skills, and further their education. I sincerely hope that all bumiputras will avail themselves of these opportunities to enhance their knowledge and facilitate their professional advancement.